Nastoiashchaia zhenshchina . Real Woman - Zhuravleva, Natalia (Russia, 2002)
Verzio FF Start: 00:52:00, End: 01:10:00 In a northern village in Russia lives a young woman who used to be a man. Rural life imposes strict social roles on the villagers, so what happens to people who do not comply with these expectations? Her father, once head of a collective farm, punished his son for wearing his mother's dress and shoes, and when her father died she felt a sense of relief. In school her classmates laughed at her, trying to understand if she was a boy or a girl. Local doctors could not help. One day she came across an article about sex-change operations and went for it. She was overjoyed to become a woman and thought all her difficulties were over, but the operation did not solve the problems of social adaptation. The decision to become a woman, which came so naturally to the protagonist, leads to isolation and mistrust from men and women alike. She longs for a harmonious family life, but will she be able to overcome the hostility of the environment?